(untitled) (Journal of Hama University, 2025)
The research aimed to identify the training needs of teachers of the first cycle of basic education in light of the requirements of the school of the future from their point of view, and to identify the differences between the average grades of teachers by identifying the training needs that relate to both the variable years of experience and academic qualifications. The research adopted the descriptive analytical method by applying a questionnaire consisting of (60) items. The research was applied in the first semester of the academic year 2024/2025 on a stratified random sample consisting of (220) male and female first-year teachers in the city of Hama. The research reached the following results: - The training needs for teachers of the first cycle of basic education, in light of the requirements of the School of the Future, from the point of view of teachers, were very high in terms of professional and life needs, and high in technical needs, communication, and communication, while moderate in technical needs (planning, implementation, and evaluation). - There are statistically significant differences regarding the training needs of teachers of the first cycle of basic education in light of the requirements of the School of the Future, due to the variable number of years of experience, due to the number of years (5-10) years. - There are statistically significant differences in the training needs of teachers of the first cycle of basic education in light of the requirements of the School of the Future due to the variable of academic qualification (At a college or institute). In light of the results, the research presented a set of proposals, including holding training courses for teachers before and during service, in order to train them on the requirements of the school of the future.